Effectiveness of Woman's Personality between the Public and Private Event the Novel Feminist Iraqi 2003 - 2013 (Journal of the College of Education for Women, 2019)
After we completed this book search we must extraction most important the findings.Event of war a majar impact on same as all human being but signed and its impact in thepsyche of iraqi woman unparalleled result of the suffering that were produced by these warsthat contributed to the destabilization of Her life at all levels a woman has lost her father,husband and son an brother as well as extreme poverty caused by the economic blockadebrought in to existence wars that exacerbated the suffering was the woman to work andeconomic in order to provide a living for her and her family and pre – empt the dreams andambitions so he excelled writer Iraqi in portraying the succession of wars that ate every thingand every body however this did not ignore for filming the events for woman of birth andrelation ship with her husband and their sense of loneliness and their need for a man and aquest proved themselves and achieve dreams that are impossible under the country's oeuvresimplest livelihoods of its citizens.